Comparison of Rocuronium and Succinylcholine for Rapid Sequence Induction in patients undergoing surgery under General Anaesthesia: Rocuronium vs Succinylcholine for rapid sequence indcution - Faisal Wahid , Aftab Hussain , Faiz-ur-Rehman , Obaid-ur-Rehman (Journal of Rawalpindi Medical College, 2020)
Objectives: To compare the frequency of excellent intubation condition with Succinylcholine and rocuronium for rapid sequence induction in patients undergoing surgery under general anesthesia. Design: Randomized control trial. Place and duration of study: Department of anesthesiology and pain medicine, Combined Military Hospital Malir Cantt Karachi from 25th June to 10th August 2019. Methodology: In this randomized control trial, a non-probability consecutive sampling technique was used. Anesthesia was given through a standard approach. Then patients were randomly divided into two equal groups. In group A, succinylcholine (1mg/Kg) was given while in group B, rocuronium (1mg/Kg) was given. Laryngoscopy was attempted after 60 seconds. Intubating conditions were labeled as excellent, good, poor, and impossible. All the data was collected in two groups, the data was entered and analyzed on SPSS version 21. Results: The mean age of the patients was 40.11±9.49 years. The male to female ratio of the patients was 0.7:1. The study results showed the excellent intubation conditions were noted in 11 from group A and 9 from group B, good intubation condition was noted in 29 from group A and 25 from group B, poor conditions were noted in 17 from group A and 16 from group B and the impossible intubation conditions were noted in 13 from group A and 20 from group B. Statistically insignificant difference was found between the study groups with intubation conditions i.e. p-value=0.570. Conclusion: It has been proved in our study that both the succinylcholine and rocuronium are statically equally effective in terms of excellent intubation conditions in the management of rapid sequence induction in patients undergoing surgery under general anesthesia.